Development of an OBE-Oriented Digital Computational Physics Practicum Module on Numerical Root-Finding Using GNU Octave - Wahyu Dian Laksanawati; Feli Cianda Adrin Burhendi; Adinda Permata Fahira (Universitas Muhammadiyah Makassar, 2026)
The rapid development of digital technology and computational systems has increased the need for physics learning resources that can strengthen students’ conceptual understanding, programming skills, and computational problem-solving abilities. In computational physics courses, students often have difficulty connecting numerical methods, algorithmic procedures, and software implementations, particularly in numerical root-finding. This study aimed to develop and determine the feasibility of an Outcome-Based Education (OBE)-oriented digital computational physics practicum module on numerical root-finding using GNU Octave. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The developed module integrates OBE-based learning outcomes, numerical root-finding concepts, numerical algorithms, GNU Octave programming tutorials, practicum worksheets, instructional videos, and learning evaluation components. The feasibility of the module was examined through material expert validation, media expert validation, a small-scale trial involving 23 Physics Education students, and a large-scale trial involving 75 students from several universities. The results showed that the material expert validation obtained an average score of 87%, while the media expert validation achieved 88%, both categorized as “Very Good.” Student responses in the small-scale trial showed percentages of 84.10% for display, 85% for material content, and 84% for video quality. In the large-scale trial, the display, material content, and video aspects obtained 85.3%, 87.78%, and 86.06%, respectively, all categorized as “Very Good.” The novelty of this study lies in integrating OBE principles with GNU Octave-based computational practicum activities into a structured digital module for numerical root-finding. The findings indicate that the developed module is feasible for supporting computational physics learning and contributes to physics education by providing an accessible, competency-oriented, and technology-based learning resource that strengthens students’ computational literacy, programming practice, and independent learning.